Large Animal Surgery Supplemental Notes - Malone, Erin (Open textbook library., 2019)
This textbook includes basic principles of large animal surgery and anesthesia, how to apply those principles to cases and situations, and discover ways of finding answers when you don’t remember the information, are presented with cases that aren’t “textbook” and/or things don’t go as planned.